2021
DOI: 10.3389/fphar.2021.626010
|View full text |Cite
|
Sign up to set email alerts
|

Role of Cannabidiol in the Therapeutic Intervention for Substance Use Disorders

Abstract: Drug treatments available for the management of substance use disorders (SUD) present multiple limitations in efficacy, lack of approved treatments or alarming relapse rates. These facts hamper the clinical outcome and the quality of life of the patients supporting the importance to develop new pharmacological agents. Lately, several reports suggest that cannabidiol (CBD) presents beneficial effects relevant for the management of neurological disorders such as epilepsy, multiple sclerosis, Parkinson’s, or Alzh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
33
0
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(43 citation statements)
references
References 224 publications
(281 reference statements)
0
33
0
4
Order By: Relevance
“…CBD was isolated more than 50 years ago, but the interest in this phytocannabinoid has increased dramatically in recent years. This compound has a very good safety profile, and preclinical and clinical studies have positioned CBD as a potential therapeutic strategy for the treatment of several neuropsychiatric disorders, including addictive disorders [ 105 , 106 ]. Besides THC and CBD, in the last few years other cannabinoids have been moved into the research spotlight to evaluate their therapeutic potential use alone or in combination with other phytocannabinoids.…”
Section: The Endogenous Cannabinoid System and Cannabinoid Compoundsmentioning
confidence: 99%
“…CBD was isolated more than 50 years ago, but the interest in this phytocannabinoid has increased dramatically in recent years. This compound has a very good safety profile, and preclinical and clinical studies have positioned CBD as a potential therapeutic strategy for the treatment of several neuropsychiatric disorders, including addictive disorders [ 105 , 106 ]. Besides THC and CBD, in the last few years other cannabinoids have been moved into the research spotlight to evaluate their therapeutic potential use alone or in combination with other phytocannabinoids.…”
Section: The Endogenous Cannabinoid System and Cannabinoid Compoundsmentioning
confidence: 99%
“…The most common cannabinoids are tetrahydrocannabinol (THC) and cannabidiol (CBD). Evidence for the health benefits of CBD suggested that the anti-inflammatory, neuroprotective, and antidepressant effects of CBD may help against psychiatric disorders, such as anxiety and insomnia, and pain [ 87 ]. Preclinical studies reported that CBD increased the survival of DGCs in mice and doublecortin-positive neuroblasts, thus promoting hippocampal neurogenesis [ 88 ].…”
Section: Therapeutic Interventions For Fear-based Disorders Via the M...mentioning
confidence: 99%
“…Cannabidiol (CBD) is a phytocannabinoid in Cannabis sativa plants, and is known for its non-psychoactive, neuroprotective, anti-convulsive, and anti-oxidative activities [ 87 ]. CBD has been reported to have neuropharmacological effects on the brain in neurological disorders, including Alzheimer’s disease, Parkinson’s disease, multiple sclerosis, epilepsy, and ALS [ 88 ].…”
Section: Anti-inflammatory and Anti-oxidative Intervention For Alsmentioning
confidence: 99%